An Analysis of Socio-economic Impact of Bt Cotton Cultivation in India - Venkatachalam, M .; Hansra, B.S.; Gowda, M. J. Chandre; Ramasubramanian, M. (Indian Journal of Extension Education, 2013)
The performance of Bt cotton and its socio-economic impact was assessed with the help of data collected from farmers of  north zone (Punjab, Haryana and Rajasthan states) and Central zone (Maharastra,Madhya Pradesh and Gujarat states).  North zone farmers received average of 10.61 q/ac from the Bt cotton and 8.03 q/ac from the cultivation of non-Bt cotton in  their field. Thus, the North zone farmers could realize an additional income from cotton yield of 2.58 q/ac (24.31 %) over  non-Bt cotton growers. Additional yield of Bt cotton over nonBt cotton of the central zone was 2.89 q/ac with tune of 26.15  per cent. The net returns from the Bt cotton cultivation (` 19,738/ac) was higher when compared to non Bt cotton  cultivation (` 9,850/ac) by the north zone respondents. A similar result was observed among the Central zone farmers as  well. The benefit cost ratio also inferred that the cultivation of Bt cotton (1:1.98) is profitable when compared to the non-Bt cotton cultivation (1:1.52). The production function analysis revealed that machine labour (hrs.), plant protection  chemicals(`/ac), irrigation (No), picking cost (`/ac)were showed positive and significant relationship with yield of Bt cotton, whereas chemical fertilizers(`/ac) and seeds(gms/ac) showed negative relationship with yield level of Bt cotton.
Keywords: Socio-economic impact; assessment; cultivation